2005
DOI: 10.1016/j.ijgo.2005.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Delivering cervical cancer prevention services in low‐resource settings

Abstract: The goals of any cervical cancer prevention program should be threefold: to achieve high coverage of the population at risk, to screen women with an accurate test as part of high-quality services, and to ensure that women with positive test results are properly managed. This article focuses on the experiences of the Alliance for Cervical Cancer Prevention (ACCP) in delivery of screening and treatment services as part of cervical cancer prevention projects in Africa, Latin America, and Asia. Research and experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 18 publications
0
44
0
5
Order By: Relevance
“…Cervical cancer is the second most common cancer among women worldwide (Bradley, 2005). The South Asian countries like India, Bangladesh, Nepal and Sri Lanka jointly contribute to nearly one-third of the global cervical cancer burden (Ferlay et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer is the second most common cancer among women worldwide (Bradley, 2005). The South Asian countries like India, Bangladesh, Nepal and Sri Lanka jointly contribute to nearly one-third of the global cervical cancer burden (Ferlay et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…26 In fact, a recent PAHO demonstration project conducted in Peru revealed that women screened with VIA were more likely to receive treatment for precancerous lesions than those screened using cytology. 27 Adequate follow-up of women with positive Pap test results has been the main challenge to the successful implementation of cytology-based programs in LAC, including Bolivia, where < 20% of eligible women receive treatment for precancerous lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the developed world, where Pap smear screening has become a routine part of women's health care, most women in developing countries have little or no access to screening or prevention services. 16 In the developed world, more than 75% of women have participated in some type of screening programme in the past five years, while less than 5% of women in the developing world have been screened. The challenges of implementing cervical cancer screening programmes include financial resource constraints, competing health needs, limited human resources, and poor infrastructure and logistical capacity of health systems.…”
Section: Service Availabilitymentioning
confidence: 99%